Keel bone fractures are more prevalent in White Leghorn hens than in Red Jungle fowl hens—A pilot study - Kittelsen, Käthe Elise (PLoS One, 2021)
Fractures and deviations to the keel bone are common in commercial laying hens, with reported variations in occurrence across strains and breeds. The aetiology is not fully understood, however, modern genetics and selection for efficient egg production has been claimed to be important factors for the keel bone fractures. To explore this further, we investigated keel bones from two different breeds, representing different degrees of selection for egg production: Red jungle fowl (n = 82), and White Leghorn (n = 32), where the latter is a selected laying breed which is the origin for many modern laying hen hybrids. Keel bones from a total of 116 birds, 53 hens and 63 roosters, were examined by necropsy at 80 weeks of age. All birds were raised in modified aviaries in the same holding facility. Overall, 24.5% of the hens had one or more fractures to the keel, with a difference in the prevalence between hens from the two breeds (p<0.01): 10% (95% CI: 3.7–24%) in the Red Jungle fowl hens and 69% (95% CI: 37–90%) in the White Leghorn hens. No roosters, regardless of breed, had keel bone fractures. Mild to moderate keel bone deviations were present in 54% (95% CI: 25–80%) of the hens and 4.7% (95% CI: 0.5–30%) of the roosters, all White Leghorns.